Implementation Of Clean and Healthy Living Behavior Efforts to Prevent the Spread of Covid 19 Padang Sambian Kelod Village - Ika Elsiani Adek; Widya Hadi Saputra I Gusti Ngurah; Oka Suryadinatha Gorda A A N (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
COVID-19 is a disease caused by a new type of coronavirus (SARS-CoV-2), which has now become a global health problem that can cause respiratory system disorders, ranging from mild symptoms such as flu to lung infections. The most effective effort currently being made is to create community awareness starting from the household level, namely through the implementation of Clean and Healthy Life Behavior (PHBS). PHBS culture is very influential in preventing the transmission of the COVID-19 virus. Through this KKN activity, it will be practiced as well as empowered by the community in implementing PHBS efforts. The data collection technique in this community service activity is in the form of socialization using interview and documentation techniques. This activity is expected to be entrenched in the community so that it can become a new habit that is not only valid during the COVID-19 pandemic but will be sustainable in the order of daily life. Increased community participation in PHBS, where people are able/empowered to make cloth masks to avoid splashing droplets when talking/coughing/sneezing and making natural hand sanitizers made from betel leaf and lime, so that they can suppress/control cases of illness and death due to COVID-19.